2019
DOI: 10.1007/s00167-018-5323-6
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin pre-soaking of the graft reduces postoperative infection rate without increasing risk of graft failure and arthrofibrosis in ACL reconstruction

Abstract: Purpose To investigate whether pre-soaking the graft in vancomycin during anterior cruciate ligament reconstruction (ACLR) reduces the postoperative infection rate and if this technique is associated with an increased rate of complications, including graft failure or arthrofibrosis. Methods A retrospective review of a prospective database was performed in 1779 patients who underwent ACLR over a period of 5 years, analysing the rate of postoperative deep knee infection. Group 1 and 2 both received perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 42 publications
5
106
0
1
Order By: Relevance
“…Our study confirmed the results of previous studies 9,10,12,13,19 in that no infection in ACL reconstruction was reported with hamstring grafts presoaked with vancomycin. The infection rate in the period immediately previous to the use of this protocol was in the upper level of the reported ranges (1.7%), while no infection was noted during the use of the protocol.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirmed the results of previous studies 9,10,12,13,19 in that no infection in ACL reconstruction was reported with hamstring grafts presoaked with vancomycin. The infection rate in the period immediately previous to the use of this protocol was in the upper level of the reported ranges (1.7%), while no infection was noted during the use of the protocol.…”
Section: Discussionsupporting
confidence: 92%
“…Offerhaus et al 10 reported a 2% postoperative deep knee infection rate without using vancomycin-presoaked grafts and a 0% infection rate when using vancomycin-presoaked grafts. In addition, they reported that the use of vancomycin did not increase the risks of graft failure, poor clinical scores, or arthrofibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have shown that vancomycin-soaked grafts are effective in preventing infection [ 5 , 13 15 , 19 , 21 ]. All published studies evaluating this subject have confirmed that none of the patients developed septic arthritis when a vancomycin-soaked graft was used.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Furthermore, other studies showed, that there is no additional risk of arthrofibrosis or graft failure by the use of vancomycin for presoaking. 26 …”
Section: Discussionmentioning
confidence: 99%